INTERNAL MARKETING: DAMPAK JOB SATISFACTION, ORGANIZATIONAL (Fokus Ekonomi, 2011)
Organizations engaged in services, the role of employees is crucial in providing customersatisfaction. This is because the process of production and consumption take place simultaneouslyon the service. Marketing services will be more easily understood approach combined elementsbetween the product and distribution, which emphasizes the dependence of mutual benefit(mutualism) between these elements. This approach allows management to focus attention on theimportance of the role of employees in serving customers. Implementing an internal marketingmanagement (internal marketing) and provide support to employees and reward goodperformance so that employees can provide a satisfactory customer service.Research uses respondent nurses and patients the highest referral general hospital in Lampungeach of 122 respondents. By using SEM (Structural Model Equetion) yields that the study supportsthe hypothesis of only three of the five hypothesized. Internal marketing in a positive effect onorganizational commitment and customer satisfaction, and job satisfaction also positivelyinfluence organizational commitment.Keywords: internal marketing, job satisfaction, organizational commitment, customerssatisfaction.